(untitled) (African Journal of Biomedical Research, 2023)
Quality patient care demands nurses to have assertive skills which depends on the level of self-esteem, however, the level of self-esteem and assertive skills and its relationship among nursing students remain understudied. This study assessed the level of self-esteem and assertive skills and their correlation among 126 Basic nursing students in Southeast, Nigeria. This was a cross sectional and correlational study. The respondents were selected using multi staged sampling technique. A questionnaire consisting of the researcher developed Socio demographic characteristics, standardized Rosenberg Self-esteem scale and Rathus assertive schedule were used for data collection. Data analysis was carried out using IBM SPSS version 23.0 software. Majority 87(69%) of the students had moderate and low 34(27%) self-esteem, only 5(4%) had high self-esteem and their average RSES scores were 17.80±4.32. Majority 95(75.4) were unassertive and their average RAE score was -.68±20.19. There was a significant positive correlation between the level of self-esteem and assertiveness (r = 0.241, p> 0. 006). Given the significant positive correlation of these variables, measures to enhance these skills in nursing student programs should be encouraged by nurse educators and managers to guarantee competent future nurse professionals.